Desenvolvimento de ligas de Mg em formas maciças para armazenagem de hidrogênio - Lima, Gisele Ferreira de (2010)
In the present work, bulk magnesium metallic hydrides (MgH2 and Mg2FeH6) were produced. Commercially pure Mg and mixtures of 2Mg-Fe were processed by severe plastic deformation (SPD) by using High Pressure Torsion (HPT) method, and also by hot extrusion. Studies were accomplished with relationship to the possibility of bulk hydrides production from those materials. Also, it was evaluated the influence of the obtained microstructure from different processing conditions and also the influence of the iron in the hydrogen sorption properties. It was verified that cycles of hydrogenation do not cause bulk disintegration in any samples. The formation of Mg2FeH6 was verified in all samples of the 2Mg-Fe mixtures. This hydride is known by the difficulty of synthesizing. In spite of the excellent results regarding the hydrogenation properties improvement and, in the ability to resist superficial oxidation, a large limitation still exists regarding the use of these results in automotive applications. Bulk hydrides were produced following the conditions studied in this work, however the kinetics is still reasonably slow and the operational temperatures are still high. This fact takes to the consideration of the verification of others possibilities of application types. In the current state of this work, the most probable application is in the static storage of hydrogen, where such problems are not so significant.